Development Of Islamic Ethnoscience Learning Model In Madrasah Ibtidaiyah - Fiteriani, Ida; Baharudin (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This research departed from facts of a science learning workshop using used goods for Madrasah Ibtidaiyah (MI) teachers. The purpose of this study was to produce an Islamic ethnoscience learning model product that was validated by experts and received responses from MI teachers in Bandar Lampung City. The research and development model uses Borg and Gall theory. The data collection technique used a questionnaire and was assisted by observation techniques, interviews, and madrasah documentation analysis. The results of validation data, then analyzed quantitatively and qualitatively. To maintain the credibility of the research results, data validity testing was carried out by 1) observation and interviews, 2) triangulation, and 3) Q&A with peers. The conclusions is Islamic ethnoscience learning model products, validated by learning model experts with a final total score of 3.3